2014
DOI: 10.1088/1367-2630/16/12/123026
|View full text |Cite
|
Sign up to set email alerts
|

Strong localization in defective carbon nanotubes: a recursive Greenʼs function study

Abstract: We study the transport properties of defective single-walled armchair carbon nanotubes (CNTs) on a mesoscopic length scale. Monovacancies and divancancies are positioned randomly along the CNT. The calculations are based on a fast, linearly scaling recursive Greenʼs function formalism that allows us to treat large systems quantum-mechanically. The electronic structure of the CNT is described by a density-functional-based tight-binding model. We determine the influence of the defects on the transmission functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 50 publications
(71 reference statements)
4
20
0
Order By: Relevance
“…It is shown that a distinction concerning (m−n)mod 3 has to be made, which discriminates three groups of CNTs with different quantitative band gap dependencies. Besides this, the localization length as well as the elastic mean free path at a given energy can be described very well by linear functions of the tube diameter, in agreement with former studies [30,32]. The investigation of CNTs of different chiral angles, covering the full range, shows that a further dependence on this structural parameter can be excluded.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It is shown that a distinction concerning (m−n)mod 3 has to be made, which discriminates three groups of CNTs with different quantitative band gap dependencies. Besides this, the localization length as well as the elastic mean free path at a given energy can be described very well by linear functions of the tube diameter, in agreement with former studies [30,32]. The investigation of CNTs of different chiral angles, covering the full range, shows that a further dependence on this structural parameter can be excluded.…”
Section: Discussionsupporting
confidence: 89%
“…Flores et al verified this for the first time with quantum transport calculations for metallic CNTs [25]. We confirmed this by a more comprehensive analysis [30] and extended it to defect mixtures [31]. An investigation of semiconducting zig-zag CNTs [32] showed qualitatively similar results for the localization and the diffusive regime at fixed energy.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…has a large impact on the electron transport [6][7][8][9][10][11][12][13], defects are in the focus of scientific work. Theoretical studies examine electronic structure and transport properties of defective CNTs, where a geometry optimization is used in order to extract the real structure of CNTs with single defects, periodic defects, or randomly distributed defects [14][15][16][17][18][19][20][21][22][23][24]. But within the geometry optimization only short CNTs are typically considered, including the shortrange reconstruction of the atoms around the defect.…”
Section: Introductionmentioning
confidence: 99%